(untitled) - James R Evans; James R Evans (Mason, Oio, 2005)
Do you know how to deliver Total Quality on the job? TOTAL QUALITY: MANAGEMENT, ORGANIZATION, AND STRATEGY not only presents the basic principles and tools associated with Total Quality, it presents them using illustrations and case studies drawn from real life scenarios. Inside, you'll read about Total Quality as it relates to privately held companies, service industry businesses, major corporations, and overseas organizations, all from the management perspective
Keywords: Total quality management